Postgraduates Perception On The Cause Of Brain Drain Among Malaysian Professionals - Ramesh Chandar, Harish Chandar (2014)
The focus of this quantitative study is to uncover the causes of brain drain among Malaysian professionals by examining the relationship between four independent variables (unattractive remuneration packages, poor opportunities for career growth, poor job satisfaction and poor quality of life) and the dependent variable (brain drain) by obtaining the perceptions of Malaysian postgraduates studying in higher institutions in Malaysia. This is because postgraduates form the cluster of the highest education level in Malaysia.